Mentalized Affectivity, Helicopter Parenting, and Psychopathological Risk in Emerging Adults: A Network Analysis - Gianluca Cruciani; Andrea Fontana; Ilaria Maria Antonietta Benzi; Lucia Sideli; Laura Antonia Lucia Parolin; Laura Muzi; Nicola Carone (MDPI AG, 2024)
Emerging adulthood represents a critical stage characterized by heightened risks for anxiety, depression, and somatization symptoms development. Research has shown that difficulties in emotional identification, expression, and processing, as well as dysfunctional parenting styles, may exacerbate symptoms in emerging adults. The present study aimed at examining the interplay between mentalized affectivity (i.e., emotional identification, processing, and expression), helicopter parenting, and psychopathological risk in 913 Italian cisgender emerging adults (M = 24.34, SD = 2.81; 71.20% assigned female at birth), using network analysis. The results indicated moderate to strong associations between psychopathological symptoms, with emotional processing difficulties significantly associated with general anxiety, depression, and, to a lesser extent, somatization. Additionally, increased degrees of helicopter parenting from mothers were linked to increased psychopathology and higher emotional processing difficulties. These findings emphasize the importance of addressing the interconnection between symptoms and emotional processing to prevent and treat psychopathological risks in emerging adults. Moreover, interventions targeting intrusive and overprotecting parenting behaviors may promote well-being among emerging adults.